HUBUNGAN DUKUNGAN ORANG TUA DENGAN KARAKTER KEMANDIRIAN SISWA KELAS IVA KURIKULUM MERDEKA - Rakhma Aulia; Arif Wiyat Purnanto; Puji Rahmawati; Nur Hiddayati (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Parents play a very important role in the development of education and character. Close coordination between family and school can help shape positive character to become the nation's next generation. The aim of this research is to determine the relationship between parental support and the independent character of class IVA MI An Nuur Cahaya Umat students. This type of research uses correlation research. The research method used was data collection using questionnaires with checklist sheets and was guided by the Likret scale. The analysis technique used is the Pearson product moment correlation from Karl Pearson with the simple help of IBM SPSS-26. The population taken in this research was 17 class IVA students at MI An Nuur Cahaya Umat. The results of the research show that to see the relationship between two variables using parametric techniques with a paired sample t test with a significance result of (0.574) and a Pearson correlation score of (0.147) with an uncorrelated category and it can be said that there is no significant relationship between parental support and character. independence. So it can be concluded from this research that the higher the support provided by parents, the lower the independent character possessed by students. On the other hand, if parental support is low, the higher the student's independent character will be.